Load simulation of a base station chassis of the mobile transport and overloading rope complex - Tarichko V.I.; Shalupina P.I. (Научно-технический вестник Брянского государственного университета)
The article deals with the issues of modeling the stress-strain state of a chassis designed to accommodate the equipment of a mobile transport and overloading rope complex. The main computational cases are determined. Geometric and computational finite element models are constructed, taking into account the features of the metal structure and suspension elements. The method of gluing elements of the grid model is applied. On the basis of the performed calculations, conclusions are drawn about the compliance of the developed structure with the requirements of strength and rigidity.